CHARITY EFFORTS OF SITI MUNJIYAH IN THE AISYIYAH ORGANIZATION IN YOGYAKARTA, 1914–1955 - Mulyati, Mulyati (Walasuji : Jurnal Sejarah dan Budaya, 2021)
Siti Munjiyah is an Aisyiyah figure who was born in Kauman, Ngupasan Village, the District of Gondomanan, Yogyakarta Province. She was one of the early generation modern women in the Dutch East Indies who had a good educationalobackground. The education he received gave a critical awareness that custom whichptook place in the.life of the community at that time hampered the progress of women's lives. This study aimed to determine the background of Siti Munjiyah's life to her participation in the movement of women in Yogyakarta. This research was a historical research because the problem revealed was focused on the past events of the life of a religious figure, named Siti Munjiyah, through her charity efforts in the Aisyiyah organization. The result study showed that Siti Munjiyah was listed as one of the figures who succeeded in advancing Aisyiyah's orthom by pioneering Frobelschool. Her work in a national scale, she became one of the participants in the First Indonesian Women's Congress in Ndalem Jayadipuran. In her speech, she gave an overview of the important of women degree. Her appearance as Aisyiyah's representative in the forum influenced the developmentSof this organization in the future. Siti Munjiyah’s opinion was very important for the progress of women in general and Muslim women in particular.